2016
DOI: 10.1371/journal.pone.0152436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Daphnia pulex in the Middle and Lower Reaches of the Yangtze River

Abstract: Increased human activities and environmental changes may lead to genetic diversity variations of Cladocerans in water. Daphnia pulex are distributed throughout the world and often regarded as a model organism. The 16S rDNA, cytochrome c oxidase subunit I (COI), and 18S genes were used as molecular marks. The genetic diversity and phylogeny of D. pulex obtained from 10 water bodies in the middle and lower reaches of the Yangtze River were studied. For 16S rDNA, COI gene, and 18S gene, the A+T content (65.4%, 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Similarly, the genetic differentiation of other Daphnia species from water bodies in the middle and lower reaches of the Yangtze River had been observed at different levels (Wang, Zhang, et al, ; Wei et al, ; Wu, Wang, et al, ). Wei et al () found that three genetically differentiated D. galeata subgroups from eight lakes in the lower reaches of the Yangtze River were observed and did not cluster by their geographical origin in overall.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly, the genetic differentiation of other Daphnia species from water bodies in the middle and lower reaches of the Yangtze River had been observed at different levels (Wang, Zhang, et al, ; Wei et al, ; Wu, Wang, et al, ). Wei et al () found that three genetically differentiated D. galeata subgroups from eight lakes in the lower reaches of the Yangtze River were observed and did not cluster by their geographical origin in overall.…”
Section: Discussionmentioning
confidence: 95%
“…Both 16S rDNA and CO I genes are two popular markers in identifying the genetic differentiation and phylogeny of Daphnia species (Ma et al, ; Ma, Petrusek, Wolinska, Hu, & Yin, ; Wang, Zhang, et al, ; Xu et al, , ). In the present study, the A + T contents were all higher than the C + G contents in the 16S rDNA and CO I gene sequences of D. galeata , which was consistent with other Daphnia species (Hebert et al, ; Wang, Zhang, et al, ; Wu, Wang, et al, ; Xu et al, ). Moreover, our results suggested that the combined analysis of the 16S rDNA and CO I gene sequences could clarify more genetic differentiation of D. galeata from water bodies located in the middle and lower reaches of the Yangtze River, China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations